Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.ejphar.2019.172475
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of GABA in neuron-glia interactions of cancer-induced bone pain

Abstract: The development of effective therapeutics for cancer-induced bone pain (CIBP) remains a tremendous challenge owing to its unclear mechanisms. Gamma-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system (CNS). Emerging studies have shown that disinhibition in the spinal cord dorsal horn may account for the development of chronic pain. However, the role of GABA in the development of CIBP remains elusive. In addition, accumulating evidence has shown that neuroglial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Central sensitisation mechanisms further involve the potentiation of NMDA receptor function, the activation of both microglia and astrocytes and the release of peptides, such as substance P [ 1 , 28 ]. Synaptic gamma-aminobutyric acid (GABA)-mediated inhibition (both at the pre- and post-synaptic level [ 36 ]) could also be impaired longitudinally by changes in GABA vesicular transport, GABA re-uptake, the alteration of intracellular chloride concentration and the modification of GABA receptor composition [ 37 , 38 , 39 ]. Indeed, aging women with osteoporotic fracture have significantly lower GABA levels [ 40 ].…”
Section: Tertiary Injury Phasementioning
confidence: 99%
“…Central sensitisation mechanisms further involve the potentiation of NMDA receptor function, the activation of both microglia and astrocytes and the release of peptides, such as substance P [ 1 , 28 ]. Synaptic gamma-aminobutyric acid (GABA)-mediated inhibition (both at the pre- and post-synaptic level [ 36 ]) could also be impaired longitudinally by changes in GABA vesicular transport, GABA re-uptake, the alteration of intracellular chloride concentration and the modification of GABA receptor composition [ 37 , 38 , 39 ]. Indeed, aging women with osteoporotic fracture have significantly lower GABA levels [ 40 ].…”
Section: Tertiary Injury Phasementioning
confidence: 99%
“…Work in a rat model of CIBP found that GABA was downregulated in CIBP rats in combination with the upregulation of GABA transporter type-1 (GAT-1) in spinal cord astrocytes ( Ge et al, 2019 ). Interestingly, administration of exogenous GAD and NO-711 (a GAT-1 specific-inhibitor) significantly reversed CIBP-induced mechanical allodynia ( Ge et al, 2019 ). This suggests that the upregulation of GABAergic signaling has the potential to be an analgesic in CIBP.…”
Section: Cys-loop Receptorsmentioning
confidence: 99%
“…Moreover, GABA displays a significant effect on the proper release of hormones and therefore the regulation of insulin so the effective treatment of diabetes (Choat et al, 2019). As well as, the desired effect of GABA on preventing the accumulation and proliferation of cancer cells and improving the healing of cancer patients with GABA utilizing has been proven (Ge et al, 2019;Schuller, 2018).…”
Section: Practical Applicationsmentioning
confidence: 99%